Histological and Histomorphometric Evaluation of Applying a Bioactive Advanced Platelet-Rich Fibrin to a Perforated Schneiderian Membrane in a Maxillary Sinus Elevation Model - Xin, Liangjing; Yuan, Shuai; Mu, Zhixiang; Li, Dize; Song, Jinlin; Chen, Tao (Frontiers in Bioengineering and Biotechnology, 2020)
Background: Schneiderian membrane perforation is a major complication of maxillary sinus elevation with simultaneous bone grafting, yet under this scenario there is no standard biomaterial that maximizes favorable tissue-healing and osteogenic effects. Purpose: To compare the effect of advanced platelet-rich fibrin (A-PRF) and collagen membrane (CM) on a perforated Schneiderian membrane (SM) with simultaneous bone grafting in a maxillary sinus elevation model. Materials and methods: After perforation of the SM was established, 24 animals were randomly divided into two groups: (i) group CM: CM and deproteinized bovine bone mineral (DBBM) (n=12), (ii) group A-PRF: A-PRF and DBBM (n=12). Radiographic and histological evaluations were performed at 1 and 4 weeks post-operation. Results: At 1 week, an intact SM was found in group A-PRF. At each time-point, the number of inflammatory cells at the perforated site was higher in group CM and the area of new osteoid formation was significantly greater in group A-PRF (p<0.0001). At 4 weeks, the osteogenic pattern was shown as from the periphery to the center of the sinus cavity in group A-PRF. Conclusions: The higher elasticity, matching degradability and plentiful growth factors of A-PRF resulted in a fully-repaired SM, which later ensured the two osteogenic sources from the SM to generate significant new bone formation. Thus, A-PRF can be considered to be a useful bioactive tissue-healing biomaterial for SM perforation with simultaneous bone grafting.